PERAN TEKNOLOGI BUDI DAYA DAN POLA TANAM PILIHAN PETANI DALAM MENINGKATKAN PRODUKTIVITAS KARET RAKYAT / Role of Cultivation Technology and Planting Patterns of Farmer Choice for Improving Smallholding Rubber Productivity - Junaidi Junaidi (Jurnal Penelitian dan Pengembangan Pertanian, 2020)
Smallholding rubber productivity in Indonesia is still relatively low due to low cultivation technology adoption. The characteristics of smallholder plantations, with limited land tenure and capital, require a specific approach compared to large plantations. This article is aimed to inform rubber cultivation innovations to improve smallholder rubber productivity. Land conservation can increase the opportunity for developing rubber in sub-optimal environments such as peatlands, tides and high-elevated areas. Plant breeding activities in Indonesia have resulted IRR superior clones series with high yield potential (more than 1,500 kg/ha/yr), vigorous growth, and resistance to main diseases. Modification of planting space can increase land productivity and alternative income for farmers during immature period. To obtain the high yield, the clonal typology harvesting system supported by latex diagnosis can optimize the potential of clones and prevent tapping panel dryness (TPD). To increase technology adoption at the farm level, the role of extension workers, farmer groups, and support from the government is required.Keywords: Rubber, farmers, technology, productivity AbstrakProduktivitas tanaman karet rakyat di Indonesia masih tergolong rendah, terutama disebabkan oleh adopsi teknologi budi daya belum optimal. Karakteristik perkebunan karet rakyat, terutama penguasaan lahan dan modal yang terbatas, memerlukan pendekatan spesifik dibanding perkebunan besar. Tulisan ini menginformasikan inovasi teknologi budidaya karet yang dapat meningkatkan produktivitas karet rakyat. Konservasi lahan dapat meningkatkan potensi pengembangan tanaman karet di lahan suboptimal seperti lahan gambut, pasang surut, dan daerah berelevasi tinggi. Pemuliaan tanaman di Indonesia telah menghasilkan klonklon unggul seri IRR dengan potensi hasil tinggi (rata-rata di atas 1.500 kg/ha/th), pertumbuhan jagur, dan tahan terhadap penyakit. Modifikasi pola tanam dapat meningkatkan produktivitas lahan dan sumber pendapatan petani selama tanaman belum menghasilkan (TBM). Untuk mendapatkan produksi yang tinggi dan berkelanjutan, sistem pemanenan lateks tipologi klon yang didukung oleh diagnosis lateks dapat mengoptimalkan potensi klon dan mencegah kering alur sadap (KAS). Untuk meningkatkan adopsi teknologi di tingkat petani diperlukan dukungan penyuluh, kelompok tani, dan pemerintah.Kata kunci: Karet, petani, teknologi, produktivitas.